Carcinogenesis - Tonissen, Kathryn (IntechOpen, 2013)
Carcinogenesis covers molecular, biochemical and cellular processes that underpin this field. The complex nature of cancer means that a broad understanding of these processes is advantageous when designing novel preventative, therapeutic or diagnostic strategies. This book commences with chapters discussing cancer predisposition and pre-cancerous lesions. Factors that initiate or progress cancer development, including viral, hormonal, oncogenic and biochemical stimuli are then described, as are interactions with the cancer extracellular environment. Animal models are particularly useful for evaluating therapeutic or chemopreventive agents and examples are presented. Finally, natural products that ether prevent or treat cancer are described. Together these topics will provide the reader with examples of the latest cutting edge research and discoveries, with the goal of stimulating further advances.